Pencegahan COVID-19 dengan pembuatan dan pembagian hand sanitizer di Universitas Muhammadiyah Palopo - Ervianingsih Ervianingsih; Chitra Astari; Izal Zahran; Hurria Hurria; Murrni Mursyid; Al Syahril Samsi (INDRA: Jurnal Pengabdian kepada Masyarakat, 2020)
The purpose of this community service activity was to educate the public to be aware of the spread of COVID-19 while maintaining cleanliness and routine hand washing using soap and running water. Using hand sanitizer is intended when around us having difficulty washing hands using soap and water. The development of the COVID-19 deployment situation caused unrest in the community. One result was panic buying or purchasing necessities and mass cleanliness, such as hand sanitizer products. Answering this, on March 22, 2020, Pharmacy Study Program at The University of Muhammadiyah (UM) Palopo took the initiative to produce hand sanitizers to adjust WHO standards.UM Pharmacy Study Program Palopo successfully produced 50 liters of hand sanitizer which was then distributed to lecturers and staff of the university. The production of hand sanitizers was also to meet the demand of Andi Djemma Palopo Airport, as the airport is one of the entry points for the spread of the COVID-19 virus. Through this community service activity, the products made are useful for overcoming the ongoing pandemic and helping to meet the needs of hand sanitizers.